#### Answer

$x\gt -63 $

#### Work Step by Step

$6x\lt7(x+9)\lt=\gt 6x\lt 7x + 63 =\gt -x\lt 63 \lt=\gt x\gt -63 $

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$x\gt -63 $

$6x\lt7(x+9)\lt=\gt 6x\lt 7x + 63 =\gt -x\lt 63 \lt=\gt x\gt -63 $

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.